Pengaruh Pengungkapan Artificial Intelligence terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi pada Perbankan terdaftar di BEI (2020-2024) - Dita Veronika; Igo Febrianto; Nindytia Puspitasari Dalimunthe (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
The banking sector has undergone dramatic changes because advances in artificial intelligence (AI) technology, which has now become essential knowledge for capital market participants. By using Good Corporate Governance (GCG) as a moderating variable, this research try to check the impact of AI disclosure on firm value in the banking industry listed on the Indonesia Stock Exchange for the years 2020–2024. Price to Book Value (PBV) as a firm value proxy, and AI Disclosure Frequency (AIFREC) is the AI disclosure metric. Company size is used as a control variable, while GCG is represented by the percentage of independent commissioners and institutional ownership. The findings demonstrate that AI disclosure significantly reduces business value, and that the relationship AI disclosure and firm value is moderated by GCG. In addition, size has a substantial negative impact on firm value, indicating that smaller banks are considered to have better growth potential while larger banks are usually at a mature stage and have lower PBV. These results highlight how AI disclosure affects the perception of the Indonesian public regarding the value of banking companies.